The characteristics of the complete chloroplast genome of Staurogyne concinnula (Hance) O. Kuntze (Acanthaceae) - Yu Mei; Dongming Chen; Shike Cai (Mitochondrial DNA. Part B. Resources, 2023)
Staurogyne concinnula (Hance) O. Kuntze (Acanthaceae) is an important ornamental herb mainly distributed in the southern region of China, including Fujian, Guangdong, Hainan, and Taiwan provinces. However, the complete chloroplast genome of S. concinnula, which could serve as a genetic resource for studies on its taxonomy and evolution, is poorly studied at present. In this study, we reported the complete chloroplast genome of S. concinnula that was assembled using high-throughput sequencing data. The chloroplast genome was 153,783 bp long, with a typical quadripartite structure containing a small single-copy region (SSC; 17,855 bp), a large single-copy region (LSC; 84,636 bp) and a pair of inverted repeats (IRs; each 25,646 bp). The overall GC content of the chloroplast genome was 38.04%. A total of 86 protein-coding genes (PCGs), 8 rRNA genes, and 37 tRNA genes were predicted. Phylogenetic analysis based on the combined sequences of 86 PCGs with the other 16 closely related species of Acanthaceae indicated that S. concinnula is closely related to Avicennia marina. The genomic data and finding from the phylogenetic studies of S. concinnula could provide useful information and give light to in-depth studies on the evolution pattern of the understudied species, as well as Staurogyne.